Lifestyle risk factors of self-reported fibromyalgia in the Norwegian Women and Cancer (NOWAC) study - Faith Owunari Benebo; Marko Lukic; Monika Dybdahl Jakobsen; Tonje Bjørndal Braaten (BMC, 2023)
Abstract Background While the aetiology of fibromyalgia syndrome (FM) remains unknown, lifestyle factors have been linked to the disorder. However, there are few studies on the association between lifestyle factors and FM, thus we examine the risk of self-reported fibromyalgia given selected lifestyle factors. Methods We used data from 75,485 participants in the Norwegian Women and Cancer study. Information on FM and the lifestyle factors body mass index (BMI), physical activity level, smoking status/intensity, and alcohol consumption were obtained from baseline and follow-up questionnaires. We used Cox proportional hazards model to calculate hazard ratios (HRs) with 95% confidence intervals (CIs). Results After a median follow-up time of 10 years, we observed 2,248 cases of self-reported fibromyalgia. Overweight (BMI 25-29.9 kg/m2) and obese (BMI ≥ 30 kg/m2) women had a relative risk of 1.34 (95% CI 1.21-1.47) and 1.62 (95% CI 1.41-1.87), respectively, compared to women with normal weight (BMI 18.5-24.9 kg/m2). Very low physical activity level (1-2) was associated with a 31% higher risk of self-reported fibromyalgia (HR 1.31, 95% CI 1.09-1.57) when compared to moderate physical activity level (5-6). There was a strong dose-response relationship between smoking status/intensity and self-reported fibromyalgia (p for trend < 0.001). Compared with moderate alcohol consumption (4.0-10 g/day), the risk of self-reported FM was 72% (HR 1.72; 95% CI 1.45-2.03) higher among teetotallers, and 38% (HR 1.38, 95% CI 1.23-1.54) higher among those with low consumption (0.1-3.9 g/day). Conclusions Overweight and obesity, very low physical activity level, smoking, and alcohol consumption were associated with an increased risk of self-reported FM.